The Social Intervention for Adolescence with Autism Spectrum Disorder (ASD): A Systematic Review - Faqihul Muqoddam; Wiwin Hendriani (Journal of Educational, Health and Community Psychology, 2019)
AbstractThe systematic review aims to find the types of effective social interventions applied to adolescents with autism spectrum disorders (ASD) in several articles selected through the screening process in 2010-2018. The review was conducted with search keywords "social intervention" and "autism spectrum disorder" on 3 online databases, namely ERIC, Springer Link, and ScienceDirect. There were 8 articles reviewed from a total of 420 obtained from screening results according to inclusion and exclusion criteria. The results showed that the social skills of adolescents with autism spectrum disorder (ASD) can be improved and developed through several interventions such as the Program for the Education and Enrichment of Relational Skills (PEERS), Multimodal Anxiety and Social Skills Intervention (MASSI), Peer Network Intervention, and CBT-CSCA. The four interventions were significantly able to increase knowledge and social skills in adolescents who experienced ASD so that it could be a reference in the intervention process in subsequent applications. While measurement with the Social Skills Rating System (SSRS) by Gresham & Elliot is the most comprehensive measurement in improving adolescent social skills. This evidenced by several articles that use this measurement and have a positive impact. The development of interventions on symbolic communication among adolescents with ASD needs to be applied in future research.Keywords: Social intervention, autism, adolescence